Effect of sintering technique on mechanical property and chemical durability of Ce0.5Pr0.5PO4 ceramics. Issue 10 (December 2015) - Ma, Jiyan; Teng, Yuancheng; Wu, Lang; Zhang, Kuibao; Huang, Yi; Zhao, Xiaofeng; Wang, Guolong
Abstract: Pr-doped monazite-(Ce) ceramics with the composition of Ce0.5 Pr0.5 PO4 were prepared by normal pressure sintering (NPS). The effects of sintering temperature and holding time on the phase structure and microstructure of ceramics were investigated. The influence of sintering process on the hardness and chemical durability of ceramics was studied. The hardness of NPS and hot-pressed (HPS) Ce0.5 Pr0.5 PO4 ceramics before and after leaching in deionised water was also examined. The results show that hardness of the HPS ceramics is higher than that of the NPS samples. The hardness reach the highest values (7.5 GPa) for HPS sample sintered at 1150 °C for 2 h, while the hardness have the maximum value (6.2 GPa) for NPS sample sintered at 1500 °C for 4 h. The hardness of HPS sample leached in deionised water is slightly improved, while the hardness of NPS sample is significantly decreased. Moreover, the leaching rates of Pr and Ce in NPS and HPS specimens decrease with increasing time and remain almost unchanged in a low value below 3.45×10 −13 m d −1, 1.27×10 –13 m d −1 after 21 days.